Triptycene‐based Chiral Porous Polyimides for Enantioselective Membrane Separation. (29th April 2021) - Zhang, Qing‐Pu; Wang, Zhen; Zhang, Zhe‐Wen; Zhai, Tian‐Long; Chen, Jing‐Jing; Ma, Hui; Tan, Bien; Zhang, Chun
Abstract: Enantiomers of 2, 6‐diaminotriptycene (R, R‐1 and S, S‐1 ) are split by chiral‐phase HPLC and their absolute configurations are identified by single‐crystal X‐ray diffraction technology. Using the enantiomers as monomers, a couple of chiral porous polyimides (R‐FTPI and S‐FTPI) are prepared by polycondensation reactions and display good heat stability, high BET surface area and good solubility in organic solvents. Moreover, both of R‐FTPI and S‐FTPI can be cast into robust, free‐standing films suitable for enantioselective separation with symmetrical chiral selectivity. Abstract : Chiral porous polyimides (FTPI) were synthesized using monomers of chiral 2, 6‐diaminotriptycene. The absolute configurations were identified by single‐crystal X‐ray diffraction. The obtained R ‐FTPI and S ‐FTPI can be cast into robust, free‐standing films suitable for enantioselective separation with high permeation rates.